IMPLEMENTASI MANAJEMEN PERTANDINGAN TIM SEPAK TAKRAW JAKARTA - Abdul Gani; Masnur Ali; Burhan Basyiruddin (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
AbstractThis community service aims to help coaches and athletes understand the challenges of implementing Match Management for the Jakarta Sepak Takraw Team and knowledge will improve the quality of coaches, because they have chosen the ability to head through the sepak takraw competition at sepak takraw coaching in the Jakarta area. The latest knowledge in training sepak takraw, especially basic and advanced besik, in providing training so that you can excel in the sepak takraw branch, especially in the Jakarta region. The implementation program will be carried out through competitions and management and workshops, in the first stage the coaches will be explained about how competition management will improve and evaluate athletes through competitions and how to increase coaching motivation. Material for the implementation of match management and the sepak takraw match program as a form of program evaluation and the formation of well-scheduled and sequential competitions. Good competitions become training targets for improving skills for sepak takraw athletes in particular, as well as increasing performance, then the types of matches and competitions so that achievements and coaching have targets as material for evaluating athletes, clubs to achieve champions and young athletes can appear at events and manage matches through community service. This community service was carried out at Cempaka Putih and the Jakarta Sports Hall. Implementation of Match Management for the Jakarta Sepak Takraw Team. This training will be held in June 1 to 2 / 2023.AbstrakSuatu pengabdian  masyarakat ini bertujuan untuk membantu para pelatih,atlit agar memahami tertantang Implementasi Manejemen Pertandingan Tim Sepak Takraw Jakarta serta  pengetahuan akan meningkatkan kualiatas pelatih, karena telah memimilih kemampuan mengepaluasi melalui melalui kompetisi sepak takraw di Pembinaan sepak takraw diwilaya Jakarta. Pengetahuan  terbaru dalam melatih sepak takraw khususnya besik dasar dan besik lanjutan dalam memberikan latihan sehinggah dapat berprestasi di cabang  sepak takraw khususnya pada lingkungan wilaya Jakarta. Program pelakasanaan akan dilakukan melalui kompetisi dan manajem  dan workshop, tahap pertama para pelatih dijelaskan tentang Akan manejemen pertandingan meningkatkan serta evaluasi atlit melalui pertandingan serta bagai mana meningkatkatkan motivasi pembinaan. Materi implementasi manajemen pertandingan serta program pertandingan sepak takraw sebagai bentuk evaluasi program dan pembentukan kompetisi yang berjejang an ter jadwal dengan baik .kompetisiyang baik menjadi target latihan untuk peningkatan keterampilan bagi atlet sepak takraw khususnya,serta peningkatan peningkatan prestasi , kemudian jenis-jenis pertandingan dan kompetisi sehingga perestasi dan pembinaan mempunyai target sebagai bahan evaluasi atlit,klub untuk meraih juara dan atlit atlit muda bisa mungcul di event pertandingan melalui pengabdian masyarakat. Pengabdian masyarakat ini dilaksanakan di Cempaka Putih dan Gedung olahraga Jakarta Implementasi Manejemen Pertandingan Tim Sepak Takraw Jakarta. Pelatihan  ini dilaksanakan pada bulan Juni tgl 1sd 2 / 2023.